English

Prove the following identities: (1 + cot θ – cosec θ)(1 + tan θ + sec θ) = 2 - Mathematics and Statistics

Advertisements
Advertisements

Question

Prove the following identities:

(1 + cot θ – cosec θ)(1 + tan θ + sec θ) = 2

Sum

Solution

L.H.S. = (1 + cot θ – cosec θ)(1 + tan θ + sec θ)

= `(1 + cos theta/sin theta - 1/sin theta)(1 + sin theta/cos theta + 1/cos theta)`

= `((sin theta+ cos theta - 1)/sin theta)((cos theta + sin theta + 1)/cos theta)`

= `((sin theta + cos theta)^2 - 1^2)/(sin theta cos theta)`       .....[∵ (a − b)(a + b) = a2 − b2]

= `(sin^2theta + cos^2theta + 2sintheta costheta - 1)/(sintheta costheta)`

= `(1 + 2sintheta costheta - 1)/(sin theta cos theta)`

= `(2sinthetacostheta)/(sintheta costheta)`

= 2

= R.H.S.

shaalaa.com
Fundamental Identities
  Is there an error in this question or solution?
Chapter 2: Trigonometry - 1 - EXERCISE 2.2 [Page 31]

APPEARS IN

RELATED QUESTIONS

Evaluate the following : 

sin 30° × cos 45° × tan 360°


Eliminate θ from the following: 

x = 3secθ , y = 4tanθ


Eliminate θ from the following : 

x = 6cosecθ, y = 8cotθ


Eliminate θ from the following :

x = 4cosθ − 5sinθ, y = 4sinθ + 5cosθ


Find the acute angle θ such that 2 cos2θ = 3 sin θ.


Find the acute angle θ such that 5tan2θ + 3 = 9secθ.


If cotθ = `3/4` and π < θ < `(3pi)/2` then find the value of 4cosecθ + 5cosθ.


Prove the following identities:

`(1 + tan^2 "A") + (1 + 1/tan^2"A") = 1/(sin^2 "A" - sin^4"A")`


Prove the following identities:

(sinθ + sec θ)2 + (cosθ + cosec θ)2 = (1 + cosecθ sec θ)2 


Prove the following identities:

`tan^3theta/(1 + tan^2theta) + cot^3theta/(1 + cot^2theta` = secθ cosecθ – 2sinθ cosθ


Prove the following identities:

`1/(sectheta + tantheta) - 1/costheta = 1/costheta - 1/(sectheta - tantheta)`


Prove the following identities:

(sec A + cos A)(sec A − cos A) = tan2A + sin2A


Prove the following identity:

1 + 3cosec2θ cot2θ + cot6θ = cosec6θ


Select the correct option from the given alternatives:

If θ = 60°, then `(1 + tan^2theta)/(2tantheta)` is equal to


Select the correct option from the given alternatives:

If cosecθ + cotθ = `5/2`, then the value of tanθ is


Select the correct option from the given alternatives:

`1 - sin^2theta/(1 + costheta) + (1 + costheta)/sintheta - sintheta/(1 - costheta)` equals


Select the correct option from the given alternatives:

If cosecθ − cotθ = q, then the value of cot θ is


Select the correct option from the given alternatives:

The value of tan1°.tan2°tan3°..... tan89° is equal to


Prove the following:  

sin2A cos2B + cos2A sin2B + cos2A cos2B + sin2A sin2B = 1


Prove the following:

`((1 + cot theta + tan theta)(sin theta - costheta)) /(sec^3theta - "cosec"^3theta)`= sin2θ cos2θ


Prove the following:

`(tan theta + 1/costheta)^2 + (tan theta - 1/costheta)^2 = 2((1 + sin^2theta)/(1 - sin^2theta))`


Prove the following:

sin4θ + cos4θ = 1 – 2 sin2θ cos2θ


Prove the following:

2(sin6θ + cos6θ) – 3(sin4θ + cos4θ) + 1 = 0


Prove the following:

cos4θ − sin4θ +1= 2cos2θ


Prove the following:

sin4θ +2sin2θ . cos2θ = 1 − cos4θ


Prove the following:

(sinθ + cosecθ)2 + (cosθ + secθ)2 = tan2θ + cot2θ + 7


Prove the following:

sin8θ − cos8θ = (sin2θ − cos2θ) (1 − 2 sin2θ cos2θ)


Prove the following:

`(1 + cot  +  "cosec" theta)/(1 - cot  +  "cosec" theta) = ("cosec" theta  + cottheta - 1)/(cottheta - "cosec"theta + 1)`


Prove the following:

`("cosec"theta + cottheta + 1)/(cottheta + "cosec" theta - 1) = cottheta/("cosec"theta - 1)`


Prove the following:

`("cosec"theta + cottheta - 1)/( "cosec"theta + cot theta + 1) =(1-sintheta)/costheta`


Prove the following identity:

`(1 - sec theta + tan theta)/(1 + sec theta - tan theta) = (sec theta + tan theta - 1)/(sec theta + tan theta + 1)`


If θ lies in the first quadrant and 5 tan θ = 4, then `(5 sin θ - 3 cos θ)/(sin θ + 2 cos θ)` is equal to ______.


Share
Notifications

Englishहिंदीमराठी


      Forgot password?
Use app×